Euthynnus lineatus Kishinouye 1920 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Euthynnus lineatus Kishinouye, 1920. Black Skipjack . To 92 cm (36.2 in) TL (Robertson and Allen 2002). San Simeon, central California (Miller and Lea 1972) to northern Peru (Chirichigno and Vélez 1998), including Gulf of California (Miller and Lea 1972), and Islas Galápagos (Eschmeyer and Herald 1983). Neritic and oceanic epipelagic; depth: surface to about 73 m (240 ft) (min.: Robertson and Allen 2002; max.: Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 211, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008